DIE JÜDIN IN WERNER TÜBKES LEBENSERINNERUNGEN DES DR. JUR. SCHULZE III (1965). (October 2014) - Hoffmann‐Curtius, Kathrin; Woodford, Charlotte; Colvin, Sarah
ABSTRACT The article will focus on Werner Tübke's artistic engagement with the Nazis' persecution of the Jews, examining the allegorical presentation of one female figure in his monumental painting Die Lebenserinnerungen des Dr. jur. Schulze III, completed in Leipzig in 1965. In his painting, Tübke uses several quotations from photography used by the SS depicting the Jewish revolt in the Warsaw Ghetto. Here, the question is asked whether and in what manner Tübke succeeded in transforming the quoted image from the Nazi years into a critical commentary on the Auschwitz trials which were taking place at the same time in Frankfurt am Main.